The anniversary: The journal “transport” – 20 years together! - Prentkovskis, Olegas (Transport, 2006)
The history of Journal “TRANSPORT” – covers, titles, ISSN, languages of publications – from 1986 to 2006 is presented. Journal's fields of research are mentioned. International databases of scientific information, which include abstracted or full text papers of Journal, are mentioned. Journal Editorial Board staff by countries is presented. Countries, from which the researchers published papers in Journal, are mentioned.First Published Online: 27 Oct 2010